KONSEP FITRAH DALAM ISLAM DAN TEORI TABULARASA DALAM PSIKOLOGI SUATU ANALISIS PERSAMAAN DAN PERBEDAAN - Linda Kurnilawati; Suriati Suriati; Salami Mahmud (NIHAYAH: Journal of Islamic Studies, 2025)
The purpose of this article is to compare the concept of fitrah in Islam and the tabularasa theory in psychology. This article is included in the literature review, using comparative study methods. The results of the research show that the concept of Islamic education and the tabularasa theory have similarities even though these two theories are different. This difference cannot be separated from the paradigm behind the two theories. The concept of fitrah views that humans are born in a clean and holy state, but is accompanied by the potential inherent in babies, such as the potential for monotheism as mentioned in the Al-Qur'an. Meanwhile, the tabularasa theory is a theory that developed in the West which views that humans are born as empty as white paper. This theory rejects the existence of innate ideas in babies, on the grounds that they cannot be proven sensory. So it can be concluded that in the concept of nature the potential that exists in babies will develop according to the environment that influences them, while in the tabularasa theory only sensory experiences obtained from the environment will fill and decorate the blank paper.